Cover Feature: Understanding the Influence of Temperature on Phase Evolution during Lithium‐Graphite (De‐)Intercalation Processes: An Operando X‐ray Diffraction Study (ChemElectroChem 2/2022). Issue 2 (16th December 2021) - Schmitt, Christina; Kube, Alexander; Wagner, Norbert; Friedrich, K. Andreas
Abstract : The Cover Feature illustrates the co‐existence of several graphite phases during delithiation at 0 °C observed by operando X‐ray diffraction. In comparison, at higher temperatures, the phase transition is faster and less phases co‐exist in case of low current measurements. More information can be found in the Article by C. Schmitt et al .